THE EFFECT OF DIFFERENTIATED LEARNING STRATEGIES ON GRADE VIII STUDENTS’ LEARNING OUTCOMES IN HUMAN RESPIRATORY SYSTEM TOPIC - Wiwin Sri Wahyuni; Sauqina Sauqina; Mella Mutika Sari (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2026)
This study aimed to examine the effect of differentiated learning strategies on Grade VIII students’ learning outcomes in the human respiratory system topic at SMPN 9 Banjarmasin. A quasi-experimental design was employed involving two intact classes: class VIII A as the experimental group (n = 31) and class VIII C as the control group (n = 35), with a total of 66 students. The experimental group received instruction using differentiated learning strategies based on content, process, and product differentiation, while the control group received conventional instruction. Data were collected using a 20-item multiple-choice learning outcome test administered as a pre-test and post-test. The instruments were validated using the Pearson Product Moment validity test, and reliability was measured using Cronbach’s Alpha. The data were analyzed using descriptive statistics, normality and homogeneity tests, ANCOVA, and the Mann–Whitney test. Because the post-test scores did not meet the homogeneity assumption, the Mann–Whitney test was used as the final hypothesis test. The results showed a statistically significant difference in post-test scores between the experimental and control groups (Sig. = 0.000 < 0.05), with the experimental group achieving a higher mean score (71.13 vs. 49.29). The ANCOVA results also indicated a large effect size for the treatment variable (partial η² = 0.354). These findings suggest that differentiated learning strategies may support students’ learning outcomes in science, particularly in the human respiratory system topic. However, the initial difference in pre-test means between the groups (46.61 vs. 33.86) should be considered a limitation when interpreting these results.